FILOSOFIS PEMIKIRAN PROF. H. M ARIFIN, M. ED. ( RELIGIUS- RASIONAL ) TENTANG PENDIDIKAN ISLAM KONTEMPORER - Ikhsan Kamil; Afifa Husnul Amin; Muhammad Fauzan (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
Abstract The thoughts of Prof. Dr. H M Arifin about his educational methods, educational goals, and educational curriculum and their relevance to contemporary (Modern) Islamic education. The relevance of Islamic education in the thoughts of Prof. Dr. H M Arifin in the contemporary realm has an interconnected approach where a basic knowledge that he takes, namely the Koran and hadith, is used as a guide in carrying out the world of education which is oriented to the present and in line with the times.